Utopia of Safe Air: How Soviet Research Challenged Western Air Quality Norms, 1950s-1960s - Mäkiranta, Janne (Oxford University Press (OUP), 2025)
During the mid-twentieth century, the Soviet Union developed ambitious hygiene standards for clean air that were grounded in extremely sensitive methods of physiological research. As Western experts sought to develop universal standards for environmental regulation, Soviet hygiene research posed a challenge. Tis article examines the discussions surrounding the Soviet approach at international conferences on air pollution and industrial hygiene during the mid-twentieth century. Te article shows that although the Soviet approach was rejected especially by United States experts, many of its qualities resonated with the ongoing discussions about environmental health in the US. Te sensitive and holistic methods of the Soviets were compelling in the efort to reveal the most subtle efects environments had on human health. Tis article shows how the rejection of Soviet standards stemmed not from diferent scientifc methods but from the diferences in the overall ideals of environmental regulation. I argue that Soviet hygiene can be seen as an extreme version of technocratic expertise, and its failure highlights the limits of scientifc expertise in managing environmental pollution.
KEYWORDS: air pollution; industrial hygiene; Soviet medicine; toxicology; environmental health; public health; occupational medicine; internationalism